How to Perform Permanent His Bundle Pacing: Tips and Tricks. Issue 12 (29th June 2016) - VIJAYARAMAN, PUGAZHENDHI; DANDAMUDI, GOPI
Abstract : Right ventricular pacing can cause ventricular dyssynchrony and result in reduced left ventricular systolic function and heart failure. Permanent His bundle pacing is a more physiologic form of pacing, but can be technically challenging. In this article, we describe our technique for permanent His bundle pacing including special considerations and limitations associated with His bundle pacing.